Evaluation of Toxoplasma and Toxocara Prevalence in Chronic Kidney Disease (CKD) Patients Using Serologic and Molecular Technique in Selected Medical Centers of Tehran, Iran - Bahare Razmand; Farid Tahvildar Biderouni; Alireza Abadi; Niloofar Taghipour (Iranian Journal of Parasitology)
Background: Toxoplasmosis and toxocariasis are two zoonotic diseases with global impact. Chronic kidney disease (CKD) can lead to complications, associated with reduced immune responses that predispose them to frequent parasitic infections. We aimed to determine the prevalence of toxoplasmosis and toxocariasis in CKD patients to propose a new way to control them in dialyses duration in Tehran, Iran. Methods: Three hundred and sixty-five CKD patients and 72 healthy individuals were tested for anti-Toxoplasma gondii (IgG, IgM) and anti-Toxocara (IgG) antibodies using conventional ELISA technique. IgM positive samples underwent genetic analysis. Results: Of the 437 samples studied (365 patients and 72 controls), 182 CKD patients (49.8%) and 20 controls (27.9%) were positive for Toxoplasma IgG, and 8 (2.2%) CKD samples were positive for Toxoplasma IgM, while none of the control samples were positive for Toxoplasma IgM. Molecular analysis of the 8 IgM positive samples with B1gene confirmed the presence of Toxoplasma antigen in all of them. Toxocara IgG antibodies showed a lower prevalence in CKD patients (5.7%) compared to controls (9.7%). The study revealed significant differences (P <0.05) in Toxoplasma IgG and IgM antibodies, as well as variables such as dialysis and dialysis duration between the two groups of patients and the control group. However, variables such as Toxocara IgG, age, gender, lupus, and pets showed no significant difference between the control group and the patients. Conclusion: The collected data in this study could serve as a reference for future studies and may be useful for examination and evaluation of acute and chronic toxoplasmosis before and after starting dialysis.